2021
DOI: 10.1186/s40621-021-00330-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of domestic violence in fatal mass shootings in the United States, 2014–2019

Abstract: Background Fatal mass shootings, defined as four or more people killed by gunfire, excluding the perpetrator, account for a small percentage of firearm homicide fatalities. Research has not extensively focused on the role of domestic violence (DV) in mass shootings in the United States. This study explores the role of DV in mass shootings in the United States. Methods Using 2014–2019 mass shooting data from the Gun Violence Archive, we indexed our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Researchers use police records and Gun Violence Archive data to categorize mass shooting risk factors, such as a prior history of violence and domestic abuse (Geller, Booty, and Crifasi 2021; The Violence Project 2022).…”
Section: The Public Health Perspectivementioning
confidence: 99%
“…Researchers use police records and Gun Violence Archive data to categorize mass shooting risk factors, such as a prior history of violence and domestic abuse (Geller, Booty, and Crifasi 2021; The Violence Project 2022).…”
Section: The Public Health Perspectivementioning
confidence: 99%
“…Several studies have found that intimate partner violence events can result in multiple victims (Kivisto and Porter 2020;Smith, Fowler, and Niolon 2014;Smucker, Kerber, and Cook 2018;Zeoli 2018). Data show that in nearly 70 percent of mass shootings from 2014 through 2019, the perpetrator either killed family or intimate partners or had a known history of DV (Geller, Booty, and Crifasi 2021). Further, research on 10 years of intimate partner homicides (IPHs) in North Carolina finds a connection between IPHs by firearm and perpetrator suicide, underscoring the potential to prevent multiple forms of gun violence by disarming domestic abusers (Smucker, Kerber, and Cook 2018).…”
Section: Protection Ordersmentioning
confidence: 99%
“…Given their statistical rarity, mass shootings present a low base rate of events that makes it difficult (if not impossible) to predict where such events will occur and who will perpetrate them (Rocque 2012). Perpetrators do share certain commonalities including histories of DV (Geller, Booty, and Crifasi 2021; Zeoli and Paruk 2020), suicidality (Lankford 2015, 2018), far-right or jihadi ideologies (Byman 2019; Dickey 2016; Lewis 2019), and other precipitative factors such as job loss, relationship problems, or other adverse childhood experiences (Dowdell et al 2022; Fowler et al 2021; Kowalski et al 2021). Many mass shooting perpetrators also struggle with mental health issues (Metzl, Piemonte, and McKay 2021), though individuals living with mental illness are more likely to be the victims rather than the perpetrators of violence (Choe, Teplin, and Abram 2008; Swanson et al 2015).…”
Section: Contemporary Approaches To the Prevention Of Mass Shootingsmentioning
confidence: 99%
“…There are strong associations between firearm access and IPV severity (Campbell et al, 2003; Sorenson & Schut, 2016; Zeoli et al, 2016), IPV and other forms of firearm violence (Geller et al, 2021; Kivisto & Porter, 2020; Smith et al, 2014; Smucker et al, 2018), and firearm violence and substance misuse (Branas et al, 2016; Hohl et al, 2017; Kuhns et al, 2014; Wintemute, 2015). This study seeks to contribute to the literature on the association between drug involvement and IPV by assessing risk among a cohort of legal handgun purchasers (i.e., individuals who were not subject to prohibitions on ownership at their times of firearm purchase in 2001).…”
Section: Introductionmentioning
confidence: 99%